Structuring of Educational Material on Discipline «World History» in Higher Education Institutions ofI- II Accreditation Levels - Andriyevska, Vita (Pedagogical Discourse, 2013)
The process of structuring of the content of world history, which is in the system forming of cognitive activity and aims at processing, target orientation of scientific information and its adaptation to the educational environment has been analyzed. The criteria and principles of selection structuring of educational material, the origin of the term «structuralism» have been studied. The impact of the process of structuring course content «World History» onto the arrangement, specification, deepening the knowledge and skills of students in colleges have been determined.